Strontium, oxygen, and carbon isotope variation in modern human dental enamel - Plomp, E. (author); von Holstein, Isabella C.C. (author); Kootker, Lisette M. (author); Verdegaal-Warmerdam, Suzanne J.A. (author); Forouzanfar, Tim (author); Davies, Gareth R. (author) (American Journal of Physical Anthropology, 2020)
Objectives: Isotopic analyses using human dental enamel provide information on the mobility and diet of individuals in forensic and archeological studies. Thus far, no study has systematically examined intraindividual coupled strontium (Sr), oxygen (O), and carbon (C) isotope variation in human enamel or the effect that caries have on the isotopic integrity of the enamel. The inadequate quantification of isotopic variation affects interpretations and may constrain sample selection of elements affected by caries. This study aims to quantify the intraindividual isotopic variation and provides recommendations for enamel sampling methods. Material and Methods: This study presents the first systematic results on intraindividual variation in Sr–O–C isotope composition and Sr concentration in modern human dental enamel of third molars (affected and unaffected by caries). A multiloci sampling approach (n = 6–20) was used to analyze surface and inner enamel, employing thermal ionization mass spectrometry (TIMS) and isotope ratio mass spectrometry (IRMS). Third molars were analyzed from 47 individuals from the Netherlands, Iceland, the United States, the Caribbean, Colombia, Somalia, and South Africa. Results: Intradental isotopic variation in modern Dutch dental elements was recorded for Sr, O, and C and exceeded the variation introduced by the analytical error. Single loci and bulk sampling approaches of third molars established that a single analysis is only representative of the bulk Sr isotope composition in 60% of the elements analyzed. Dental elements affected by caries showed twice the variation seen in unaffected dental elements. Caries did not consistently incorporate the isotopic composition of the geographical environment in which they developed. Discussion: The isotopic variability recorded in unaffected inner enamel indicates that variations greater than 0.000200 for 87 Sr/ 86 Sr and larger than 2‰ for δ 18 O and δ 13 C are required to demonstrate changes in modern Dutch human diet or geographic location. ...